Effects of Various Forage Systems on Grazing and Subsequent Finishing Performance - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 200 mixed black yearling steers were used to compare grazing and subsequent finishing performance from pastures with ‘MaxQ’ tall fescue, a wheat-bermudagrass double-crop system, or a wheat-crabgrass double-crop system in 2010, 2011, 2012, 2013, and 2014. Daily gains of steers that grazed ‘MaxQ’ tall fescue, wheat-bermudagrass, or wheat-crabgrass were similar (P>0.05) in 2010, daily gains of steers that grazed wheat-bermudagrass or wheat-crabgrass were greater (P>0.05) than those that grazed ‘MaxQ’ tall fescue in 2011 and 2012, daily gains of steers that grazed wheat-crabgrass were greater (P>0.05) than those that grazed wheat-bermudagrass and similar (P>0.05) to those that grazed ‘MaxQ’ fescue in 2013, and daily gains of steers that grazed wheat-crabgrass were greater (P>0.05) than those that grazed wheat-bermudagrass or ‘MaxQ’ fescue in 2014. Finishing gains were similar (P>0.05) among forage systems in 2010, 2012, 2013, and 2014. In 2011, finishing gains of steers that grazed ‘MaxQ’ tall fescue were greater (P<0.05) than those that grazed wheat-bermudagrass.
Keywords: grazing; fescue; crabgrass; bermudagrass; finishing